Identification of Intestinal NaCl Absorptive-Anion Secretory Cells: Potential Functional Significance - Donowitz, Mark; Sarker, Rafiquel; Lin, Ruxian; McNamara, George; Tse, Chung Ming; Singh, Varsha (Frontiers in Physiology, 2022)
Use of human enteroids studied in the undifferentiated and differentiated state that mimic the intestinal crypt and villus, respectively, has allowed studies of multiple enterocyte populations, including a large population of enterocytes that are transitioning from the crypt to the villus. This population expresses NHE3, DRA, and CFTR, representing a combination of Na absorptive and anion secretory functions. In this cell population, these three transporters physically interact, which affects their baseline and regulated activities. A study of this cell population and differentiated Caco-2 cells transduced with NHE3 and endogenously expressing DRA and CFTR has allowed an understanding of previous studies in which cAMP seemed to stimulate and inhibit DRA at the same time. Understanding the contributions of these cells to overall intestinal transport function as part of the fasting and post-prandial state and their contribution to the pathophysiology of diarrheal diseases and some conditions with constipation will allow new approaches to drug development.